New Record of Neopicrorhiza minima R.R.Mill (Plantaginaceae) to the Flora of India - Dipankar Borah; Rajeev Kumar Singh (Mongolian Journal of Biological Sciences)
Neopicrorhiza minima, an endemic and rare herb of Bhutan is reported for the first time from India (Tawang district of Arunachal Pradesh state). The species was known only from the type localities in Bhutan since 1933. It grows in boggy soil among mosses and grasses, near water bodies of Himalayan Alpine grassland, in association with Cassiope fastigiata, Corydalis cashmeriana, Galearis roborovskii, Gentiana pedicellata, Saxifraga hispidula, Saussurea obvallata. Extended taxonomic description, habitat, phenology, notes and colour photographs are provided.